The effect of low-dose intravenous bisphosphonate treatment on osteoporosis in children with quadriplegic cerebral palsy - Soon Jeong Moon; Young Min An; Soon Ki Kim; Young Se Kwon; Ji Eun Lee (Korean Pediatric Society, 2017)
PurposeQuadriplegic children with cerebral palsy are more susceptible to osteoporosis because of various risk factors that interfere with bone metabolism. Pamidronate is effective for pediatric osteoporosis, but there are no guidelines for optimal dosage or duration of treatment in quadriplegic children with osteoporosis. We aimed to evaluate the efficacy of low-dose pamidronate treatment in these patients.MethodsTen quadriplegic patients on antiepileptic drugs (6 male, 4 female patients; mean age, 10.9±5.76 years), with osteoporosis and gross motor function classification system level V, were treated with pamidronate (0.5-1.0 mg/kg/day, 2 consecutive days) every 3-4 months in a single institution. The patients received oral supplements of calcium and vitamin D before and during treatment. The lumbar spine bone mineral density (BMD) z score and biochemical markers of bone metabolism were measured regularly during treatment.ResultsThe main underlying disorder was perinatal hypoxic brain damage (40%, 4 of 10). The mean cumulative dose of pamidronate was 4.49±2.22 mg/kg/yr, and the mean treatment period was 10.8±3.32 months. The BMD z score of the lumbar spine showed a significant increase from −4.22±1.24 before treatment to −2.61±1.69 during treatment (P=0.008). Alkaline phosphatase decreased during treatmentn (P=0.037). Significant adverse drug reactions and new fractures were not reported.ConclusionLow-dose pamidronate treatment for quadriplegic children with cerebral palsy increased lumbar BMD and reduced the incidence of fracture.